2017
DOI: 10.1186/s13045-017-0507-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LIN28B impairs leukemia cell growth and metabolism in acute myeloid leukemia

Abstract: BackgroundCurrent conventional chemotherapy for acute myeloid leukemia (AML) can achieve remission in over 70% of patients, but a majority of them will relapse within 5 years despite continued treatment. The relapse is postulated to be due to leukemia stem cells (LSCs), which are different from normal hematopoietic stem cells (HSCs). LIN28B is microRNA regulator and stem cell reprogramming factor. Overexpression of LIN28B has been associated with advance human malignancies and cancer stem cells (CSCs), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…For example, LIN28A enhances translation of IGF2 by recruiting translation initiation complexes (Polesskaya et al, ). Some reports have shown that LIN28B functions as an oncogene in several cancers (Meder et al, ; Zhou et al, ). It has been shown in GC cells, that LIN28B directly binds to neuropilin‐1 (NRF‐1) 3′UTR and enhances its mRNA stability (X. Wang, Hu, et al, ).…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 99%
“…For example, LIN28A enhances translation of IGF2 by recruiting translation initiation complexes (Polesskaya et al, ). Some reports have shown that LIN28B functions as an oncogene in several cancers (Meder et al, ; Zhou et al, ). It has been shown in GC cells, that LIN28B directly binds to neuropilin‐1 (NRF‐1) 3′UTR and enhances its mRNA stability (X. Wang, Hu, et al, ).…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 99%
“…We previously reported that human AML cell line TF-1a cells express abundant endogenous LIN28B protein[ 19 ]. In order to investigate the relationship between NF-κB and LIN28B, we treated the TF-1a cells with gradual concentrations of Bortezomib and MG-132, two different NF-κB inhibitors[ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The images were captured using Konica Medical SRX‐101A Medical Film Processor (Konica Minolta Medical & Graphic, Inc., Wayne, NJ, USA). Densitometric analysis was performed using Amersham Image Scanner with labscan imagequant tl Software (Amersham Biosciences, Piscataway, NJ, USA) (Zhou et al ., ). The protein levels of each molecule were normalized with each respective actin level.…”
Section: Methodsmentioning
confidence: 99%
“…IMAGEQUANT TL Software (Amersham Biosciences, Piscataway, NJ, USA) (Zhou et al, 2017). The protein levels of each molecule were normalized with each respective actin level.…”
Section: Scanmentioning
confidence: 99%